A study of “rational use of investigations” in a tertiary hospital - Gulab Kanwar; Shivprakash Rathore; Arpit Khandelwal; Khandelwal, Divya; Ankur Khandelwal; Rajmal Meena; Manna Lal Kumawat (Asian Journal of Medical Sciences, 2022)
Background: Rational laboratory use is defined as effective and correct laboratory use by providing the most appropriate test selection with the right clinical approach in line with the evidence-based data and considering the cost and patient safety. The present study was thus conducted for the prevalence and features associated with rational use of investigations in a tertiary hospital. Aims and Objectives: The objectives of the study were to estimate prevalence of rational use of investigations and its associated confounding factors; to explain the educational approach underlying the study; and to explain how to teach rational approach of investigations so that we reduce the use of unnecessary and inappropriate tests which are not likely to have any ill effects on the patient. Materials and Methods: A cross-sectional study including 100 patients was selected by random sampling from medicine and orthopedic wards and OPD. Results: In our study,we observed 29 different types of clinical and laboratory investigations out of 2155 investigations ordered by physicians before any intervention. These investigations done in 100 patients, among those 39.16% were contributed to the management of patients and 60.83% were not considered to have contributed toward management of patients. Conclusion: Several external and internal factors can promote irrational use of investigation at different stages. Hence, understanding these factors and implementing appropriate measures are key steps to change behavior of prescriber and nursing staff. We must have logic-based flow chart or algorithm in all investigations for diagnosis as a part of good laboratory or good clinical practices.